Operation and sustainability of Water, Sanitation and Hygiene (WASH) in schools: Evidence from a vulnerable and deprived area in Ghana - Anthony Acquah Mensah; Dina Adei; Godfrey Kuubagr; Samuel Ofori Duah; Michael Osei Asibey (Taylor & Francis Group, 2022)
Abstract: Safe and adequate water supply and sanitation in schools are pre-requisites for the right to basic education for school children and the achievement of goal 4 and 6 of the Sustainable Development Goals. Nonetheless, Water, Sanitation and Hygiene (WASH) in schools is fraught with inadequacy of toilet and handwashing facilities, and poor sustainability mechanisms that threaten its success. This paper, therefore, assesses the operation and sustainability of WASH in schools in the Nabdam District of Ghana. Adopting a qualitative approach, thirty-seven semi-structured interviews were held to capture the understanding and experiences of students, head teachers, health officers, officials of the Ghana Health Service and District Education Directorate on the phenomena. Fifteen focus group discussions were further held with students in the basic schools. The findings indicate that WASH is poorly managed even though the schools studied had some established WASH facilities. WASH in the schools was bedeviled with challenges such as inadequate toilets and handwashing facilities, poor funding and ineffective WASH committees. The WASH committees lacked the capacity to raise funds and carry out their duties in accordance with the WASH implementation guidelines. The study recommends that the Ghana Education Service organizes periodic capacity building programs for WASH committees to address this shortcoming. The Ministry of Education should support basic schools in districts in their efforts to provide WASH facilities and fund WASH activities. The study also calls for the formation of student WASH clubs and sanitation brigades to promote the operation and sustainability of WASH in schools.